Controlled release of optimized electroporation enhances the transdermal efficiency of sinomenine hydrochloride for treating arthritis in vitro and in clinic - Feng S; Zhu L; Huang Z; Wang H; Li H; Zhou H; Lu L; Wang Y; Liu Z; Liu L (Dove Medical Press, 2017)
Shun Feng,1,* Lijun Zhu,1,* Zhisheng Huang,2 Haojia Wang,1 Hong Li,1 Hua Zhou,3 Linlin Lu,1 Ying Wang,1 Zhongqiu Liu,1,3 Liang Liu1,3 1International Institute for Translational Chinese Medicine, Guangzhou University of Chinese Medicine, Guangzhou, Guangdong, 2Department of Acupuncture and Rehabilitation, Guangzhou Hospital of Integrated Traditional Chinese and Western Medicine, Guangzhou, Guangdong, 3State Key Laboratory of Quality Research in Chinese Medicine, Macau University of Science and Technology, Macau, People’s Republic of China *These authors contributed equally to this work Abstract: Sinomenine hydrochloride (SH) is an ideal drug for the treatment of rheumatoid arthritis and osteoarthritis. However, high plasma concentration of systemically administered SH can release histamine, which can cause rash and gastrointestinal side effects. Topical delivery can increase SH concentration in the synovial fluid without high plasma level, thus minimizing systemic side effects. However, passive diffusion of SH was found to be inefficient because of the presence of the stratum corneum layer. Therefore, an effective method is required to compensate for the low efficiency of SH passive diffusion. In this study, transdermal experiments in vitro and clinical tests were utilized to explore the optimized parameters for electroporation of topical delivery for SH. Fluorescence experiment and hematoxylin and eosin staining analysis were performed to reveal the mechanism by which electroporation promoted permeation. In vitro, optimized electroporation parameters were 3 KHz, exponential waveform, and intensity 10. Using these parameters, transdermal permeation of SH was increased by 1.9–10.1 fold in mice skin and by 1.6–47.1 fold in miniature pig skin compared with passive diffusion. After the electroporation stimulation, the intercellular intervals and epidermal cracks in the skin increased. In clinical tests, SH concentration in synovial fluid was 20.84 ng/mL after treatment with electroporation. Therefore, electroporation with optimized parameters could significantly enhance transdermal permeation of SH. The mechanism by which electroporation promoted permeation was that the electronic pulses made the skin structure looser. To summarize, electroporation may be an effective complementary method for transdermal permeation of SH. The controlled release of electroporation may be a promising clinical method for transdermal drug administration. Keywords: electroporation, sinomenine hydrochloride, transdermal drug delivery, arthritis